The effects of low and controlled traffic systems on soil physical properties, yields and the profitability of cereal crops on a range of soil types - Chamen, W. C. T. (Cranfield University, 2011)
Soil compaction is an inevitable consequence of mechanised farming systems whose machines are degrading soils to the extent that some are considered uneconomic to repair. A number of mitigating actions have been proposed but their ability to reduce or avoid damage has not been well tested. The aim of this research was to determine whether actions to reduce damage have been, or are likely to be effective and to assess whether the practice of controlled traffic farming (confining all field vehicles to the least possible area of permanent traffic lanes) has the potential to be a practical and cost effective means of avoidance. The literature confirmed that soil compaction from field vehicles had negative consequences for practically every aspect of crop production. It increases the energy needed to establish crops, compromises seedbed quality and crop yield, and leads to accelerated water run-off, erosion and soil loss. It is also implicated in enhanced emissions of nitrous oxide and reduced water and nutrient use efficiency. Replicated field trials showed that compaction is created by a combination of loading and contact pressure. Trafficking increased soil penetration resistance by 47% and bulk density by 15% while reducing wheat yield by up to 16%, soil porosity by 10% and infiltration by a factor of four. Low ground pressure systems were a reasonable means of compaction mitigation but were constrained due to their negative impact on topsoils and gradual degradation of subsoils whose repair by deep soil loosening is expensive and short lived. Controlled traffic farming (CTF) was found to be practical and had fundamental advantages in maintaining all aspects of good soil structure with lowered inputs of energy and time. On a farm in central England, machinery investment with CTF fell by over 20% and farm gross margin increased in the range 8-17%.